2017
DOI: 10.18203/2349-3291.ijcp20173787
|View full text |Cite
|
Sign up to set email alerts
|

To study the role of probiotics in the prevention of necrotizing enterocolitis in preterm neonates

Abstract: Background: Necrotizing enterocolitis is defined as an inflammatory bowel necrosis in premature infants and is major cause of morbidity and mortality in neonatal intensive care units throughout the world. We aim to study the role of probiotics in reducing incidence and severity of necrotizing enterocolitis in preterm neonates ≤34 weeks and its role on secondary outcomes like mortality, time to reach full feeds, daily weight gain, days of hospitalization and effect on nosocomial infections.Methods: This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
3
14
1
Order By: Relevance
“…In our present study, the incidence of NEC was significantly lower in the test group compared with the control group (1 of 30 neonates versus 4 of 30 neonates; p<0.001). Similar observations were seen in studies by Lin et al, Angela, Bin-Nun et al, Lin et al, Janvier et al and Khurana et al 8,13,14,17,18,20 However studies conducted by Dani et al, Costalos et al and Manzoni et al found a lower incidence of NEC in the probiotic group, but this did not reach statistical significance. 7,15,16…”
Section: Incidence Of Necsupporting
confidence: 84%
“…In our present study, the incidence of NEC was significantly lower in the test group compared with the control group (1 of 30 neonates versus 4 of 30 neonates; p<0.001). Similar observations were seen in studies by Lin et al, Angela, Bin-Nun et al, Lin et al, Janvier et al and Khurana et al 8,13,14,17,18,20 However studies conducted by Dani et al, Costalos et al and Manzoni et al found a lower incidence of NEC in the probiotic group, but this did not reach statistical significance. 7,15,16…”
Section: Incidence Of Necsupporting
confidence: 84%
“…After excluding duplicates, 648 records were screened, of which 576 were excluded due to not meeting the inclusion criteria. Finally, 51 studies assessing the effects of 29 different probiotic interventions were eligible for inclusion in the systematic review and primary NMA [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 <...>…”
Section: Resultsmentioning
confidence: 99%
“…Only 18 studies reported NEC according to feeding type during the study period: ten studies reported NEC in exclusively HM-fed infants [ 29 , 33 , 40 , 51 , 53 , 62 , 64 , 70 , 74 , 76 ], either the mother’s own (MOM) or donor human milk (DHM), five studies included exclusively formula-fed infants [ 34 , 36 , 55 , 69 , 77 ], one study included infants who received HM plus FM [ 46 ] and two studies reported outcome according to different feeding types [ 37 , 57 ]. Separate data according to type of feeding were provided by e-mail for 13 of these studies [ 28 , 39 , 44 , 45 , 48 , 56 , 58 , 63 , 66 , 67 , 68 , 72 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations